Assessment and analysis of plant vegetation under oil palm from 2000 and 2017 plantation - Yenni, Asbur; Yayuk, Purwaningrum; Dedi, Kusbiantoro; Khairunnisyah, Nasution; Dian, Hendrawan; Fiqi Alfisar, Lubis (Plant Science Today, 2025)
Intensive use of chemicals in agricultural cultivation such as fertilizers and pesticides has caused a decline in plant diversity in agricultural ecosystems in recent decades. This study aims to determine the diversity of weeds and dominant weeds in oil palm plantations in the planting years 2000 and 2017. The research was carried out from January to June 2023 at the oil palm plantation PT Perkebunan Nasional III, Kebun Sei Putih, North Sumatra using the 1 m ? 1 m quadratic method. In oil palm stands in the 2000 planting year, the grass weed Cirtococcum oxyphyllum was found as the dominant weed with a high importance index and Summed Dominance Ratio (SDR), while in oil palm stands in the 2017 planting year, the broadleaf weed Ageratum conyzoides was found as the dominant weed. Species diversity (H') under oil palm stands in the 2000 planting year ranged between 0.67-1.61, which means that species diversity is low to moderate, and in 2017 planting year ranged between 1.34-1.64, which means that species diversity is moderate. The community coefficient value for both planting years was low, namely below 75 percent, which means that the weed community in both planting years was very diverse.